Algunos micro elementos en la nutrición animal - Davis, G. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Work with trace elements from all parts of the world has emphasized that the results of one area cannot be transferred directly to another area. Every locality which has livestock should be checked for the mineral elements needed by livestock of that locality. The symptoms described in this report may serve as a guide to the investigations that should be made. However, the similarity of deficiency symptoms and the lack of definite symptoms in sub-clinical deficiencies should encourage both practical animal husbandmen and scientific investigators to undertake careful tests of the needs of livestock for trace elements in any given locality.